الجريمة السياسية بين الشريعة الإسلامية و التشريع الجزائري - أحمد رامي عولمي (My University, 2021)
Abstract: Political crime is a crime with both political and legal dimensions, this is what led to the great ambiguity that sparked widespread controversy among scholars due to the multiplicity of their intellectual orientations in different periods of time, and this crime is closely linked to the higher and general interests of the State in various political systems whether in societies that ruled on the basis of religion or those that we see today and govern on the basis of man-made laws, including Algeria, when referring to the Islamic civilization that has actually been proactive in putting in place a criminal system to fight this kind of crime, which is known as a prostitute that targets the rule in the state and tries to overthrow it through the motives and interpretations of the perpetrators as well as the manifestations of power that they invest in order to overthrow the ruler and control the reins of government, this is undoubtedly a cause for chaos and vandalism. Therefore, Islam has confronted this type of crime through provisions on how to deal with an offence even before it occurs; this indicates the perfection of Sharia and its encompassing all the security means required to establish a rational rule. At the level of Algerian law, the presence of political crime has been linked to many factors, including historical, political and social. Nowadays, the forms of political crime have evolved greatly which led the legislature to adapt to this development and to enact a set of deterrent texts for these deadly crimes, which are aimed at the internal and external structure and security of the State, by addressing the various acts that constitute this crime of conspiracy, murders and sabotage against the security of the state and acts described as terrorism which causes security and political instability in the country at the internal level in addition to other types of foreign threats to the State, the crime of espionage and treason committed by Algerian and foreign nationals where the legislator discriminated on the basis of the offender's nationality. Algeria's attempt to develop its legal arsenal was not indiscriminate, but was linked to events that Algeria experienced in the near past from political and security conflicts and unrest. It prompted the legislator to make amendments with qualitative precedence in the legal field, such as the amendment issued under Order No. 95-11 that addressed a new type of political crime represented by acts described as terrorist acts and subsequent amendments. However, it is noticeable that compared to Islamic law, the legal texts lack the flexibility and coverage that characterize Sharia which the legislator had to pay attention to and increase the effectiveness of legal texts by taking from Islamic Sharia as a source of law. ................... الملخص : تعد الجريمة السياسية من الجرائم ذات البعدين السياسي و القانوني، هذا ما أدى إلى الغموض الكبير الذي أثار جدلا واسعا لدى الفقهاء بتعدد توجهاتهم الفكرية في مختلف الحقب الزمنية، ذلك أن هذه الجريمة ترتبط ارتباطا وثيقا بمصالح الدولة العليا و العامة في مختلف الأنظمة السياسية، سواء في المجتمعات التي حكمت على أساس الدين أو تلك التي نراها اليوم و تحكم على أساس القوانين الوضعية والتي منها الجزائر ، قعند الرجوع للحضارة الإسلامية التي كانت سباقة في الحقيقة لوضع منظومة جنائية لمحاربة هذا النوع من الجرائم والذي عرف بالبغي، الذي يستهدف الحكم في الدولة و يحاول الإطاحة بالحاكم والسيطرة على مقاليد الحكم ، فهذا مما لاشك فيه أنه مدعاة للفوضى والتخريب لذلك فقد تصدى الإسلام لهذا النوع من الجرائم من خلال أحكام تبين كيفية التعامل مع الجريمة حتى قبل وقوعها، وهذا يدل على كمال الشريعة وإحاطتها بكافة سبل الأمن المطلوبة لإقامة حكم راشد. أما على صعيد القانون الجزائري فقد ارتبط تواجد الجريمة السياسة بالعديد من العوامل منها التاريخي ومنها السياسي و منها الاجتماعي، وقد تطورت وتعددت صور الجريمة السياسية حاليا بشكل كبير مما دفع المشرع إلى التأقلم مع هذا التطور، وسن مجموعة من النصوص الرادعة لهذه الجرائم الفتاكة التي تستهدف كيان الدولة وأمنها على المستوى الداخلي و الخارجي من خلال التطرق لمختلف الأفعال التي تشكل هذه الجريمة من جرائم مؤامرة و جرائم تقتیل و تخریب مخلة بأمن الدولة و فعال موصوفة بالإرهاب، والتي تتسبب بزعزعة الاستقرار الأمني و السياسي في الدولة على المستوى الداخلي، بالإضافة إلي أنواع أخرى تهدد الدولة على الصعيد الخارجي من جرائم تجسس و خيانة التي يقترفها الجزائري و الأجنبي حيث ميزة فيها المشرع على أساس جنسية الجاني. إن سعي الجزائر تتكتوير ترسانتها القانونية لم يكن عشوائيا، إنما ارتبعط بأحداث عاشتها الجزائر بالأمس القريب من صراعات و اضطرابات سياسية وأمنية جعلت المشرع يقوم بتعديلات ذات أسبقية نوعية في المجال القانوني، كالتعديل الصادر بموجب الأمر رقم 95-11 الذي تصدي لنوع جديد من الجرائم السياسية الذي تمثل في الأفعال الموصوفة بالأفعال الإرهابية و ما تلا ذلك من تعديلات، إلا أن الملاحظ أنه مقارنة بالشريعة الإسلامية فإن النصوص القانونية تفتقر للمرونة والإحاطة التي تتميز بها الشريعة والتي كان لا بد على المشرع أن ينتبه لها ويزيد من فعالية النصوص القانونية بالأخذ من الشريعة الإسلامية باعتبارها مصدرا من مصادر القانون. ..................... Résumé : Le crime politique est un délit à dimension politique et juridique. Ce crime est étroitement lié aux intérêts de l’État suprême et du public dans divers systèmes politiques. dans les sociétés qui ont gouverné sur la base de la religion ou celles que nous voyons aujourd’hui et gouvernent sur la base de lois positives, y compris l’Algérie, au moment du retour à la civilisation islamique, qui était en fait un précurseur de la mise en place d’un système pénal pour lutter contre ce type de crime, connu sous le nom de prostitution qui vise à régner dans l’État et tente de renverser le gouverneur et de prendre le contrôle des rênes du gouvernement, C’est sans aucun doute une cause de chaos et de vandalisme, de sorte que l’islam a abordé ce type de crime par des dispositions montrant comment traiter le crime avant même qu’il ne se produise. Cela démontre l’intégrité de la Charia et l’informe de tous les moyens de sécurité nécessaires à l’établissement du pouvoir de Rashid. En droit algérien, l’existence d’un crime politique a été liée à de nombreux facteurs, dont l’histoire, politique et sociale. le crime politique a évolué et le crime politique s’est considérablement multiplié, amenant les législateurs à s’adapter à cette évolution, Adoption d’une série de dispositions visant à dissuader ces crimes mortels qui visent l’entité de l’État et sa sécurité aux niveaux interne et externe en s’attaquant aux divers actes qui constituent des crimes de conspiration et des crimes qui tuent et sabotent une violation de la sécurité de l’État et un efficace qualifié de terrorisme. la sécurité et l’instabilité politique dans l’État au niveau interne, En outre, d’autres types d’infractions d’espionnage et de trahison commis par l’Algérie et l’étranger menacent l’État au niveau étranger, dans lequel l’avantage du législateur est basé sur la nationalité de l’auteur. La poursuite par l’Algérie de son arsenal juridique n’a pas été aveugle, mais a été liée aux événements que l’Algérie a connus hier à proximité de conflits et de bouleversements politiques et sécuritaires qui ont conduit le législateur à apporter des amendements de primauté qualitative dans le domaine juridique. Comme l’amendement publié par l’ordonnance no 95-11 pour traiter d’un nouveau type de crime politique qui constitue des actes décrits comme des actes terroristes et des modifications subséquentes. Cependant, par rapport à la charia islamique, les textes juridiques manquent de souplesse et de discrétion.